Medication errors in Pediatric Intensive Care Unit: incidence, types and outcome - Saeedeh Haghbin; Sina Shahsavari; Afsaneh Vazin (Shiraz University of Medical Sciences, 2016)
Medication Errors (MEs) play a significant role in mortality and morbidity of hospitalized patients. Therefore, it seems advisable to determine types and consequences of such errors when addressing patient safety. The aim of this study was to determine the incidence, types, outcomes of errors in a 10 bed pediatric Intensive Care Unit at a large teaching hospital from September 2013 to February 2014 in southern Iran.The occurrence of errors was detected with direct observation method. A trained pharmacist selected 41 patients randomly in forty one working shifts. No patient arrived the study twice. In each shift, patient's medications were observed from prescription, administration, transcription, and dispensing. The pharmacist would intervene only if the ME could cause substantial harms to a patient. All data were reviewed by a clinical pharmacist and a pediatric intensivist to confirm the type of the errors.Of the 512 drug dosages observed, 48.8 errors/100 orders were detected, Administration errors occurred on 148 occasions, with 28.9 chances to occur in each 100 orders. Prescription, transcription and dispensing errors came next with 14.25, 4.88 and 0.78 chance in each 100 orders, respectively. Wrong time, wrong technique, and wrong preparation were among the commonest types of administration errors with 14.1%, 5.7% and 4.9%, respectively.  Monitoring errors group with 11.3% was the most common type of prescribing errors.The results of this study highlights the high medication error rates in pediatric ICU under the study, with administration and prescription errors marked the highest share of them.  Hence implementing the effective strategies to reduce them are needed.